2018
DOI: 10.5430/ijba.v9n3p30
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Financial Behavior Among Accounting Students in Bali

Abstract: This study was aimed at analyzing factors that influence financial behavior among accounting students in Bali. This study used the quantitative approach through distributing questionnaires and a financial literacy test. The sample was selected through the multistage random sampling technique with the sample size of 518 respondents. The data were analyzed by using multiple regression analysis. The results of the study showed that there is a positive and significant effect of financial literacy, financial self e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
53
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 2 publications
15
53
1
12
Order By: Relevance
“…In agreement with the survey above, students' comprehension of investment in the stock market is relatively low. That was also mentioned in several types of researches which showed that students' understanding of investment had the lowest average compared to understanding financial management, credit financing, and retirement fund [4,5]. The lack of understanding of investment makes students' interest in investing become low as well.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the survey above, students' comprehension of investment in the stock market is relatively low. That was also mentioned in several types of researches which showed that students' understanding of investment had the lowest average compared to understanding financial management, credit financing, and retirement fund [4,5]. The lack of understanding of investment makes students' interest in investing become low as well.…”
Section: Introductionmentioning
confidence: 99%
“…A good financial behavior such as paying the bill on time, savings and having investment and ability to control credit card usage wisely can be influenced by an individual with a good financial literacy [19]. Financial behavior may be affected by the financial literacy of an individual [17]. The other research findings by [20] showed that good financial behavior significantly influences the level of financial literacy.…”
Section: Problem Statementmentioning
confidence: 99%
“…Financial management amongst university students helps to prepare themselves in the future. Students who are far from their families will face problems in managing their finance because they need to learn how to manage things on their own including their financial [17]. In addition, the ability to control financial resources is important in their daily life activities.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of developing learning assessment components and learning outcomes, this study will utilize on the existence of five entrepreneurial education competency standards to measure the entrepreneurial education outcomes for diploma and strata students in the field [5]. As for the implementation of micro-based learning administration services management activities, this study will adapt the results of the implementation of a website-based multimedia learning model to foster an entrepreneurial culture in universities reference by [3].…”
Section: Literature Reviewmentioning
confidence: 99%